An investigation of Norwegian students’ affective domain in mathematics - Kislenko, Kirsti (NOMAD Nordic Studies in Mathematics Education, 2009)
After decades of research in the affective domain in mathematics education, and search for ways to enhance students’ positive attitudes towards the discipline, the perception that to be able to do mathematics is innate remains a widespread belief. Already twenty years ago the Fourth NAEP study concluded that students believe mathematics to be important, difficult and based on rules, and theses attributions also characterise the view of mathematics even two decades later. As a relationship exists between the claims ”mathematics is difficult” and ”mathematics is boring” one could assume that students lack interest towards mathematics. The conclusions about the present situation are based on a study carried out in Norway in 2005. This paper documents and analyses the data from the study. Six factors are identified and analysed in relation to students ́ affective domain in mathematics. The six factors are: interest, hard-working, self-confidence, usefulness, insecurity, and MAD (Mathematics as an Absolute Discipline).